Gravitational instability of rotating magnetized quantum anisotropic plasma. (9th March 2017) - Argal, Shraddha; Tiwari, Anita; Prajapati, R. P.; Sharma, P. K.
Abstract : The present problem deals with the study of gravitational (Jeans) instability of magnetized, rotating, anisotropic plasmas considering quantum effects. The basic equations of the considered system are constructed using combined Chew–Goldberger–Low (CGL) fluid model and quantum magnetohydrodynamic (QMHD) fluid model. A dispersion relation is obtained using the normal mode technique which is discussed for transverse and longitudinal modes of propagation. It is found that a rotating quantum plasma influences the gravitational mode in transverse propagation but not in longitudinal propagation. The presence of rotation decreases the critical wavenumber and it has a stabilizing effect on the Jeans instability criterion of magnetized quantum plasma in transverse propagation. The firehose instability is unaffected due to the presence of uniform rotation and quantum corrections. We observe from the numerical analysis that region of instability and critical Jeans wavenumber are both decreased due to the presence of uniform rotation. The stabilizing influence of uniform rotation is observed for magnetized, rotating, anisotropic plasmas in the presence of quantum correction. In the case of a longitudinal mode of propagation we found the Jeans instability criterion is not affected by rotation. The quantum diffraction term has a stabilizing effect on the growth rate of the Jeans instability when the wave propagates along the direction of the magnetic field.